Exploring the concept of strategy as practice in national disaster risk reduction: the case of Botswana - Dennison, Margaret Opelo (University of the Witwatersrand, Johannesburg, 2024)
Many communities in Botswana are prone to disaster threat; natural, man-made and technological, and unfortunately, evidence suggests that there are weaknesses in the Botswana’s disaster risk reduction and disaster management system. These weaknesses can have a negative impact on preventative efforts, increasing disaster impacts on societies. The key research question for this study is: How is strategy implementation done for national disaster risk reduction in Botswana and what improvements can be made using the Strategy- as practice lens? The extant literature does not explore how disaster risk reduction is done from first hand experiences of those on the ground. In contrast to traditional organisational strategic management, strategy in practice considers the process in which individual interactions and interpretations of organisational strategy lead to enactment of strategy on the ground. The study is qualitative and exploratory. The sample was selected from all three levels of the Botswana disaster risk management institutional framework. A purposive sampling technique was used, and two participants were selected from the National Disaster Management office, 6 District Commissioners and 34 participants from 6 District Disaster Management Committees based on their level of responsibility. 35 Village Development Committee Chairpersons from umbrella committees were also included in the sample as they represent a wider population within their districts. In addition, snowball sampling was used to select 11 Chairpersons from ordinary Village Development Committees. Data collection used document review, semi- structured interviews, focus groups and the nominal group technique. Findings indicate that there is no extant formal disaster risk management legislation in the country meaning there are no legally required risk management systems in place. As a result, disaster risk reduction in the past has been conducted without effective communication and coordination of disaster risk reduction strategies and systems at national, district and village levels. The study recommends that disaster risk management legislation, sufficient training for implementors at all levels of the disaster risk management institutional framework as well as coordination and communication strategies and systems should be put in place to effectively deal with mitigating disasters that the country may face in the future.
A research report submitted in fulfillment of the requirements for the Doctor of Philosophy (Business Sciences- Management), In the Faculty of Faculty of Commerce, Law and Management, School of Business Sciences, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; DISASTER RISK REDUCTION; DISASTER RISK MANAGEMENT; DISASTER MANAGEMENT; STRATEGY AS PRACTICE; STRATEGIC MANAGEMENT; SDG-17: Partnerships for the goals